Feeling Worse Before Feeling Better: A Case of Increased Disorganized Mental States Following Group Psychotherapy. Issue 2 (3rd April 2017) - Tasca, Giorgio A.; Maxwell, Hilary; Faye, Megan; Balfour, Louise
ABSTRACT: Is group therapy effective if it results in members revealing greater unresolved/disorganized mental states related to childhood trauma? That is, do patients have to more fully experience partially disavowed trauma before they get better? We found a small proportion of patients whose pre-treatment Adult Attachment Interview (AAI) transcripts were not coded as Unresolved/Disorganized at the start of group treatment, but were coded as such at the end. In one case report, we examined pre- and six months post–AAI transcripts and group therapy interactions to document the emergence of an unresolved/disorganized mental state. Despite the increase in disorganization, the patient showed some symptom improvement and improved reflective functioning. The 16-week psychodynamic group therapy allowed the patient to reflect on her traumatic experiences and their impact on her life. However, this also resulted in a disorganizing effect on her mental state. Longer-term therapy may be necessary to improve interpersonal functioning and affect regulation in patients who experienced early trauma.